Unitarian Universalist Association of Congregations social justice grants. Issue 382 (10th June 2021) - Unknown
Abstract : The Unitarian Universalist Association of Congregations supports community organizing campaigns aimed at creating systemic change in the economic, social and political structures that affect the lives of those who have been excluded from resources, power and the right to determination.